The roles of AIM2 in neurodegenerative diseases: insights and therapeutic implications - Yang, Kai; Wang, Xi; Pan, Hanyu; Wang, Xinqing; Hu, Yunhan; Yao, Yihe; Zhao, Xinyue; Sun, Taolei (Frontiers in Immunology, 2024)
AIM2, a cytosolic innate immune receptor, has the capability to recognize double-stranded DNA (dsDNA). This paper delineates the structural features of AIM2 and its mechanisms of activation, emphasizing its capacity to detect cytosolic DNA and initiate inflammasome assembly. Additionally, we explore the diverse functions of AIM2 in different cells. Insights into AIM2-mediated neuroinflammation provide a foundation for investigating novel therapeutic strategies targeting AIM2 signaling pathways. Furthermore, we present a comprehensive review of the roles of AIM2 in neurodegenerative diseases, including Alzheimer's disease (AD) and Parkinson's disease (PD). Finally, we discuss its therapeutic implications. In conclusion, a profound understanding of AIM2 in neurodegenerative diseases may facilitate the development of effective interventions to mitigate neuronal damage and slow disease progression.